A Stocking Diagram for Even-aged Mixed Pine-Fir Stands of Kastamonu Region - Kara, Ferhat; Altunel, Arif Oguz (Turkish Journal of Engineering, 2025)
Forest stand density diagrams help forest managers and practitioners more effectively manage stand density and tree occupancy to meet specific silvicultural goals. Therefore, creating such auxiliary silvicultural tools for different stands is essential. To our knowledge, no relative density graphs or diagrams have been developed for mixed stands in Türkiye. This study aimed to develop a stocking diagram for mixed Scots pine (Pinus sylvestris L.)-Kazdağı fir (Abies nordmanniana subsp. equi-trojani) stands. In the study, statistical relations between stocking percent and diameter increment in selected sample plots were also determined, and these statistical relations were compared with the "stand basal area-diameter increment relations" in the same sample plots. Stand stocking percent was found to be more descriptive than absolute density measurement units (i.e., basal area) in defining stand density in mixed Scots pine-Kazdağı fir stands. The resulting stock diagram may allow more effective use of stand growing space to achieve various silvicultural goals, including regeneration, thinning, and wildlife protection in mixed Scots pine- Kazdağı fir stands. Depicting various density measures including basal area, trees per ha, and stand stocking percent, the findings of this study would facilitate the tree density management in mixed Scots pine- Kazdağı fir stands.
Keywords: Abies; Absolute density; Pinus; Relative density; Silviculture; Çevre Mühendisliği (Diğer); Environmental Engineering (Other)